2014
DOI: 10.18544/pedm-20.04.0013
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the P1 promoter of the IGF-1 gene in children with growth disorders

Abstract: This study demonstrated that SNP and (CA) n microsatellite repeat polymorphisms by themselves are not the primary regulatory elements of IGF-1 expression. However, our bioinformatics analysis has shown that the (CA) n microsatellite region in the P1 promoter of IGF-1 is able to form DNA loop structures which can modulate transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(42 reference statements)
1
2
1
Order By: Relevance
“…Few studies have explored the relationship between genetic variations in the IGF system and the risk of SPTB. A previous study conducted in Chile found that IGF1 rs5742612 was associated with SPTB risk, while this SNP was reported to have no correlation with the levels of circulating IGF1 . In the present study, women with GA or GA/AA genotypes of IGF1 rs972936, which is located in intron region, had an increased risk of SPTB compared to those with the GG genotype.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Few studies have explored the relationship between genetic variations in the IGF system and the risk of SPTB. A previous study conducted in Chile found that IGF1 rs5742612 was associated with SPTB risk, while this SNP was reported to have no correlation with the levels of circulating IGF1 . In the present study, women with GA or GA/AA genotypes of IGF1 rs972936, which is located in intron region, had an increased risk of SPTB compared to those with the GG genotype.…”
Section: Discussioncontrasting
confidence: 59%
“…A previous study conducted in Chile found that IGF1 rs5742612 was associated with SPTB risk, 18 while this SNP was reported to have no correlation with the levels of circulating IGF1. [19][20][21] In the present study, women with GA or GA/AA genotypes of IGF1 rs972936, which is located in intron region, had an increased risk of SPTB compared to those with the GG genotype. A previous study of European Alzheimer's disease patients showed that individuals with AG and AA genotypes of IGF1 rs972936 had lower serum IGF1 levels compared to those with the GG genotype.…”
Section: Discussionsupporting
confidence: 44%
“…Differently, Broniarczyk et al . found that rs35767, rs5742612 polymorphisms in promoter region of IGF1 didn't affect serum IGF1 level in children with growth disorders [ 22 ]. Kanbur and Sesti et al reported that rs35767 was associated with changes of IGF1 level [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the MMS type was only detected in the serum of 22.2% and in the tissue of 9.0% of patients with EC. A previous bioinformatics study by our group showed that the CA repeat region of the P1 promoter of IGF-1 is able to form DNA loop structures, which may serve as a recognition site for transcriptional modulators of the IGF-1 gene ( 38 ). Thus, changes in the number of CA repeats may have an influence on IGF-1 promoter activity and be associated with EC; however, further studies are required to confirm this.…”
Section: Discussionmentioning
confidence: 99%